Filamentous growth is a general feature of Candida auris clinical isolates. (23rd January 2021) - Fan, Shuru; Yue, Huizhen; Zheng, Qiushi; Bing, Jian; Tian, Sufei; Chen, Jingjing; Ennis, Craig L; Nobile, Clarissa J; Huang, Guanghua; Du, Han
Abstract: A striking feature of pathogenic Candida species is morphological plasticity that facilitates environmental adaptation and host infection. Candida auris is an emerging multidrug-resistant fungal pathogen first described in Japan in 2009. In this study, we demonstrate that clinical isolates of C. auris have multiple colony and cellular morphologies including the yeast, filamentous, aggregated, and elongated forms. This phenotypic diversity has been observed in eight clinical isolates of C. auris representing four major genetic clades, suggesting that it could be a general characteristic. We further demonstrate that different cell types of C. auris exhibit distinct antifungal resistance and virulence properties in a Galleria mellonella infection model. Our findings imply that morphological diversity is an important biological feature of C. auris and could be a contributor to its emergence and rapid prevalence worldwide. Lay Summary: Candida auris is an emerging multidrug-resistant fungal pathogen. Morphological analyses indicate that filamentation is a general feature of clinical isolates of C. auris . This ability is associated with antifungal resistance and virulence.